Contribution of maximum entropy principle in the field of queueing theory - Parkash, Om; Mukesh (Communications in statistics. Theory and methods, 2016)
In the literature of information theory, there exist many well known measures of entropy suitable for entropy optimization principles towards applications in different disciplines of science and technology. The object of this article is to develop a new generalized measure of entropy and to establish the relation between entropy and queueing theory. To fulfill our aim, we have made use of maximum entropy principle which provides the most uncertain probability distribution subject to some constraints expressed by mean values.